Differences in severity of cardiovascular anomalies in children with Noonan syndrome based on the causative gene - Shehade-Awwad, Nagham; Yeshayahu, Yonatan; Pinhas-Hamiel, Orit; Katz, Uriel (Frontiers in Pediatrics, 2022)
Background: Noonan syndrome (NS) is a genetic syndrome, characterized by various dysmorphic features, cardiac anomalies, short stature, and developmental delay. NS is a leading cause of cardiovascular anomalies. The syndrome results from dysregulation in the RAS-MAPK pathway and is related to the RASopathy family syndromes. Pathogenic variants in more than 20 related genes have been identified in association with NS, and several genotype-phenotype correlations were suggested. The specific severity of the same cardiovascular anomalies has not been described as linked to a specific causative gene. Methods: For this retrospective, single-center study, data retrieved from medical charts of a multidisciplinary NS clinic included genetic diagnosis, cardiac malformations, the need for intervention, demographics, and prenatal diagnosis. We analyzed molecular genetics and the severity of cardiac malformations. Results: The cohort comprised 74 children with NS. Consistent with previous studies, pathogenic variants in PTPN11 were the most common (62%). Cardiovascular anomalies presented in 57%; pulmonary stenosis (PS) was the most common (about 79% of anomalies). In children with pathogenic variants in PTPN11, PS tended to be more severe and required intervention in 53%, compared to 25% of children with PS and a variant in other genes. Conclusion: This first Israeli cohort of NS showed similar rates of cardiac malformations and genetic breakdown as previously published. Variants in PTPN11 were prone to a higher risk for severe PS that requires intervention. This finding may assist in genetic counseling and cardiac treatment decisions, and stresses the importance of genetic in addition to clinical diagnosis of NS.